A New Symmetrical Far Infrared Nebula at -33° Declination - Aryal, B; Simkhada, K; Rajbahak, C; Weinberger, R (Scientific World, 2010)
A systematic search at far infrared wavelength in IRAS (Infrared Astronomical Satellite) survey using Groningen Server is performed and investigated a new symmetrical far-infrared (~3° x 2°) filamentary emission at R.A. (J2000) = 21h28m51s and Dec. (J2000) = -33°53'23''. The softwares ALADIN2.5 and ASTROLINUX5.0 are used for the data reduction. We have performed multiwavelength study in the region of interest. The physical properties, flux density, temperature and mass of the nebula are estimated and discussed. In the multiwavelength study, the optical and ultraviolet emission is found to be negligible. A significant far infrared emission is noticed. The radio and X-ray emission is observed to be moderate. It is found that there is a maxima in each filaments, that can clearly seen in 60 μm and 100 μm wavelengths. This indicates that the structure is nearby and a strong external force is influencing its shape. No star is forming in our region of interest. Our symmetrical far infrared nebula belongs to category II type cloud, appearing as diffuse emission of nearly faint optical surface brightness but showing a clumpy structure with no star forming. Total mass of the gas of our nebula is found to lie in the range 1.275 - 3.000 x 103 Msun. This estimation is based on the results of flux density study assuming a distance 150±50 pc and dust color temperature 25±5 K. Key Words: Interstellar Medium; Stars; Nebula; Infrared Emission. DOI: 10.3126/sw.v7i7.3815 Scientific World Vol.7(7) 2009 pp.3-9